An examınatıon of the anxıety states of Turkısh health care workers durıng the COVID-19 pandemıc: a cross-sectıonal study - Ceylan,Ali (2022)
SUMMARY OBJECTIVE: The aim of this study was to evaluate the anxiety experienced by health care workers in different branches during the COVID-19 pandemic. METHODS: The cross-sectional study included 373 health care workers. Data were collected using an online questionnaire consisting of the Sociodemographic Form (32 items related to the working conditions of health care professionals during the COVID-19 pandemic) and the Penn State Concern Questionnaire. RESULTS: The anxiety levels of the female workers were significantly higher (p<0.001). The total Penn State Concern Questionnaire points were determined to be statistically significantly higher in those who need to protect the family during the pandemic (p=0.03), who were dissatisfied with their profession (p<0.001), and those whose workload had increased during the pandemic (p=0.007). CONCLUSIONS: The study results demonstrated that the levels of anxiety of health care workers during the COVID-19 pandemic could be increased by young age, low level of experience, female gender, increased workload, and dissatisfaction with the profession.